Rising complexity and falling explanatory power in ecology. Issue 7 (20th August 2014) - Low-Décarie, Etienne; Chivers, Corey; Granados, Monica
Abstract : Analyses of published research can provide a realistic perspective on the progress of science. By analyzing more than 18 000 articles published by the preeminent ecological societies, we found that (1) ecological research is becoming increasingly statistically complex, reporting a growing number of P values per article and (2) the value of reported coefficient of determination ( R 2 ) has been falling steadily, suggesting a decrease in the marginal explanatory power of ecology. These trends may be due to changes in the way ecology is studied or in the way the findings of investigations are reported. Determining the reason for increasing complexity and declining marginal explanatory power would require a critical review of the scientific process in ecology, from research design to dissemination, and could influence the public interpretation and policy implications of ecological findings.